Losing one's hand: visual-proprioceptive conflict affects touch perception. - Alessia Folegatti; Frédérique de Vignemont; Francesco Pavani; Yves Rossetti; Alessandro Farnè (PLoS ONE)
Background While the sense of bodily ownership has now been widely investigated through the rubber hand illusion (RHI), very little is known about the sense of disownership. It has been hypothesized that the RHI also affects the ownership feelings towards the participant's own hand, as if the rubber hand replaced the participant's actual hand. Somatosensory changes observed in the participants' hand while experiencing the RHI have been taken as evidence for disownership of their real hand. Here we propose a theoretical framework to disambiguate whether such somatosensory changes are to be ascribed to the disownership of the real hand or rather to the anomalous visuo-proprioceptive conflict experienced by the participant during the RHI. Methodology/principal findings In experiment 1, reaction times (RTs) to tactile stimuli delivered to the participants' hand slowed down following the establishment of the RHI. In experiment 2, the misalignment of visual and proprioceptive inputs was obtained via prismatic displacement, a situation in which ownership of the seen hand was doubtless. This condition slowed down the participants' tactile RTs. Thus, similar effects on touch perception emerged following RHI and prismatic displacement. Both manipulations also induced a proprioceptive drift, toward the fake hand in the first experiment and toward the visual position of the participants' hand in the second experiment. Conclusions/significance These findings reveal that somatosensory alterations in the experimental hand resulting from the RHI result from cross-modal mismatch between the seen and felt position of the hand. As such, they are not necessarily a signature of disownership.